2013
DOI: 10.15376/biores.8.4.5219-5234
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Layered Structure on Physical and Mechanical Properties of Kenaf Core Particleboard

Abstract: Kenaf (Hibiscus cannabinus), a fast-growing fiber crop, is a potential substitute for wood to make composition boards. This work investigated single-and three-layer kenaf core particleboards (KPBs) and kenaf core-cedar wood composite particleboard (KCPB) with polymeric methylene diphenyl diisocyanate (pMDI) and phenol formaldehyde (PF) resins. The physical and mechanical properties including bending modulus (MOE) and strength (MOR), internal bond (IB) strength, water absorption (WA), thickness swelling (TS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Studies have been conducted to find the suitable agrofibers for composite manufacturing (Bektaş et al 2005). Some of the agrofibers studied so far are cotton and hemp stalks (Kollmann 1966), groundnut shell (Jain et al 1967), bagasse (Mitlin 1968;Turreda 1983), grain-wheat straw (Mosesson 1980;Han et al 1998), bamboo (Rowell and Norimoto 1998), tea plant waste (Nemli and Kalaycioğlu 1997;Yalinkiliç et al 1998;Filiz et al 2011;Batiancela et al 2014), sunflower stalks (Khristova et al 1998;Bektaş et al 2005), vine branches (Ntalos and Grigoriou 2002), castor stalks (Grigoriou and Ntalos 2001), corn stalks (Güler et al 2001), wheat straw and corn stalks (Wang and Sun 2002), kiwi branches (Nemli et al 2003), peanut shell (Batalla et al 2005), almond shells (Gürü et al 2006), agricultural waste (Arslan et al 2007), giant reed (Garcia-Ortuna et al 2011), kenaf (Xu et al 2013), kenaf and rubberwood (Abdul Halip et al 2014), sunflower seed husks (Cosreanue et al 2015), and hazelnut husk (Avcı et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted to find the suitable agrofibers for composite manufacturing (Bektaş et al 2005). Some of the agrofibers studied so far are cotton and hemp stalks (Kollmann 1966), groundnut shell (Jain et al 1967), bagasse (Mitlin 1968;Turreda 1983), grain-wheat straw (Mosesson 1980;Han et al 1998), bamboo (Rowell and Norimoto 1998), tea plant waste (Nemli and Kalaycioğlu 1997;Yalinkiliç et al 1998;Filiz et al 2011;Batiancela et al 2014), sunflower stalks (Khristova et al 1998;Bektaş et al 2005), vine branches (Ntalos and Grigoriou 2002), castor stalks (Grigoriou and Ntalos 2001), corn stalks (Güler et al 2001), wheat straw and corn stalks (Wang and Sun 2002), kiwi branches (Nemli et al 2003), peanut shell (Batalla et al 2005), almond shells (Gürü et al 2006), agricultural waste (Arslan et al 2007), giant reed (Garcia-Ortuna et al 2011), kenaf (Xu et al 2013), kenaf and rubberwood (Abdul Halip et al 2014), sunflower seed husks (Cosreanue et al 2015), and hazelnut husk (Avcı et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the density of kenaf stem was much denser compared to the core and can also be processed into fine particles that is suitable for making particleboards. Kenaf (Hibiscus cannabinus L.) is a non-wood fiber crop that comes from Africa [6]. Kenaf is a fast-growing species and was introduced to Malaysia bio-composite industry by the National Kenaf and Tobacco Board (NKTB).…”
Section: Introductionmentioning
confidence: 99%
“…It contains a higher lignin content and less cellulose compared to the bast fiber. Bast fiber contains over 44.4 % cellulose, 21.1 % lignin, 2.7 % extractives and 4.6 % ash [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%